CHARACTERISTICS OF QUARTZ SAND MATERIAL AND ASSOCIATED MINERALS FORM THE BY-PRODUCT OF ALLUVIAL TIN PROCESSING IN BANGKA AND BELITUNG ISLANDS, INDONESIA - Dwi Utami, Shelia
The quartz sand which contain of SiO2 (silicon dioxide) and other tin-related minerals are among the numerous final products of tin processing. SiO2 is widely utilized in various industries at different levels. The distribution of SiO2 content and sizes is quite diverse. In this study, we try to clarify the characterization of quartz sand and tin-associated minerals using grain counting analysis (GCA) in five blocks in Bangka and Belitung Islands, Indonesia, which yielded notable values that are useful for further exploration and mineral processing. As a result, we found that in Block A, the SiO2 content has a relatively high value for sizes -30 mesh to +140 mesh, reaching 99.4%. In Block B, the SiO2 content has a relatively high value for size +30 mesh, spanning 97.5%. We reported that in Block C and Block E, the SiO2 content has a relatively high value for sizes -30 mesh to +140 mesh, approaching 99.1% and 99.2%, respectively. The same condition was also reported in Block D, which has a relatively high value of SiO2 for size +30 mesh, spreading to 99.4%. We found that the presence of tin-associated minerals in each block was dominated by tourmaline and ilmenite. The final product of SiO2 material has potential applications such as low-iron silica sand, molding sand, and gravel pack sand, as following the Minister of Trade Regulation Number 12 Year 2022 in Indonesia. Nonetheless, further study is needed to evaluate other criteria such as clay content, roundness, sphericity, Fe2O3 content, and water content.